COUNTERING RADICALISM THOUGHT ON ISLAM A Study of Ibrahim M Abu Rabi's Thought - Muh. Mustamsikin; ghufron hamzah (Pascasarjana Universitas Wahid hasyim Semarang, 2021)
The terrorist event and the destruction of the sea alms tradition in Bantul recently were quite surprising, because as we know that Yogyakarta is rich in cultural traditions. The phenomenon of violence with greater religious motives also occurred in Indonesia, such as the Bali Bombing on October 12, 2002, and more violent was the September 11, 2001 event at the WTC United States. The question is why does an understanding arise that justifies acts of terrorism in the name of religion? What is the solution offered by Ibrahim M Abu Rabi 'in responding to the phenomenon of terrorism in the name of religion? This paper will explain the thoughts of Ibrahim M Abu Rabi 'about the importance of re-examining the nature of Islamic thought when there are many Western accusations that the teachings of Islam legalize acts of violence and terrorism. Abu Rabi took three approaches in starting his study; (1) starting with the historical development of Islamic modernization, (2) education in the Islamic world, and (3) contemporary elites and the rise of religion in the Arab world. The philosophical, critical theological, socio-historical, and anthropological approaches to the study of Islam that were implied by Abu Rabi to bring Islam to the advanced conditions become accumulated in interconnected integrative ways of thinking. Keywords: Ibrahim M Abu Rabi ', Radicalism, Terorism, and Integrative Interconnection.